Process of the administration, innovation and internationalization of textile artisanal companies of the Puno region - Aliaga-Melo, Grisell (2022)
The purpose of the research is to determine the measure of relationship between the process of administration and innovation with the internationalization of textile exporting companies in the Puno Región, specifically to demonstrate the measure of correlation between the process of administration and innovation. with internationalization, and quantify the level of compliance with the internationalization indicators. The methodology was a non-experimental design, quantitative approach, deductive method, descriptive-correlational and explanatory in scope, with a sample of 27 companies, the technique was the survey and the instrument was the questionnaire. There is an average positive correlation between the administration process with internationalization, reflected in the Spearman correlation coefficient whose value was 0.564 [p<0.01]. There is a weak positive correlation between innovation and internationalization, reflected in the Spearman correlation coefficient, which was 0.451 [p<0.05]. The level of compliance with the internationalization indicators was calculated through the development of an internationalization index (IdI) using the principal component analysis (PCA) method, evidencing a "poor" rating for the characteristic dimensions of the environment and development. exporter, "regular" for the dimensions internal factors and resources and capabilities and "good" for the dimensions characteristic of the entrepreneur and characteristics of the sector.